Fatigue behavior and NDE characteristic of aluminum silicon-carbide metal-matrix composites using ultrasonic pulse-echo method - Nunez, Ricarte C.
A study was conducted to investigate the removal of benzene and toluene vapors from a synthetically prepared waste air stream through microbial degradation in a trickle-flow bioreactor packed with an exceptionally simple and inexpensive fibrous medium consisting of a coiled sheet of cotton terry cloth. The fibrous packing exhibited excellent characteristics for interphase mass transfer and biofilm attachment such as high static liquid holdup, high porosity, large specific surface area and high moisture retention capacity, maintained its structural integrity even after more than a year of continuous bioreactor operation, and allowed simple and stable operation and ease of control of back pressure, liquid holdup, and flooding. Liquid phase residence time distribution analysis showed continuous liquid film flow through the fibrous bed without droplet formation, low to intermediate liquid dispersion, fairly uniform velocity profile and flow path, and no significant liquid channeling nor stagnation. Benzene and toluene removal from waste air streams, ascribed to biological degradation alone and not to some other mechanisms, progressed independently from each other. Pre-acclimatization, the presence of benzene-degrading species such as Pseudomonas putida and P.fluorescens, and the ideal environment (e.g., absorbent and porous packing) for microbial attachment and growth within the bioreactor resulted in rapid bioreactor startup of 3 days. The bioreactor performed best with aqueous medium recycle at a rate just enough to maintain a wet biofilm (~1.43 L/h) due to high gas-liquid mass transfer area and low mass transport resistance of thin liquid film, and partial wetting of the packing. Excess biomass was controlled by limiting the amount of NH₄+-N in the aqeous recycle medium or by manually removing the packing from the bioreactor, scraping it free of excess biomass, and washing in water. The bioreactor was able to recover quickly from transient conditions such as a very low pH of 3, total depletion of NH₄+-N in the aqueous recycle medium, and cleaning. During treatment of an air stream containing 1:5 (by volume) toluene/benzene mixed vapors, the bioreactor achieved eleimination capacities for toluene and benzene of 25.8 g/m³-h (98% removal) and 79.2 g/m³-h (99.7% removal), respectively, at 1.39 min empty bed gas contact time and 1.43 L/h aqueous medium recycle rate
Thesis (Ph.D. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Metallic composites -- Fatigue; Metallic composite -- Testing; Ultrasonic testing